PENILAIAN KESEHATAN BANK DENGAN PENDEKATAN RISIKO (RISK BASED BANK RATING) - Asnina, Siska Fitriya; Sapari, Sapari (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This main aims of this study is to assess rate of health commercial bank is carried out by using Risk BasedBank Rating approach or it is commonly called as Risk Profile, Good Corporate Governance, Earning, andCapital (RGEC) method. This research applies descriptive qualitative. The result is the risk profile factor whichis measured by using 2012-2014 NPL ratio which shows that the bank is in a very good condition with theaverage value is â¤ 2% every year. The 2012-2014 LDR ratio shows that the bank is in good condition with theaverage value is 82%-84% every year. The assessment of 2012-2014 GCG factor shows that the bank is in goodcondition even though there are some banks in quite well and less good in 2012. The rentability factor which ismeasured by using 2012-2014 ROA and NIM ratios show the average result of the assessment that the bank isin good condition every year. The capital factor which is measured by using CAR shows that in 2012-2014periods the bank is in a very good condition every year.Keywords: good corporate governance, bank health, risk approach, financial ratio.